Growth crystallography of silicon phases in unmodified impurity and chill modified AI-Si eutectic alloys - Engku Mohd. Nazim Engku Abu Bakar; Asian Conference on X-Rays and Related Techniques in Research and industry (1996 : Ipoh, Malaysia)
20